The United States and the Middle East: What Comes Next After Iraq? - Fares Center for Eastern Mediterranean Studies (Tufts Archival Research Center, 2005)
Occasional Paper No. 4; A report on the conference The United States and the Middle East: What Comes Next After Iraq?, March 27-28, 2008, Tufts University, Medford/Somerville, MA.